Kinetic Study of the hydrolysis of p-Anisidine Phosphoric Triamide (C—N—P) in Acid Medium - Sahni, V.; Prabha, S. (Asian Journal of Chemistry, 2010)
Hydrolytic fragmentation of tri-p-anisidine orthophosphate has been pursued in the acid range 1.0 to 8.0 M-HCI in 20% acetic acid (v/v) at 65ºC (±0.5ºC). Neutral electrolyte effect study reveals the contribution of conjugate acid form with the absence of any participation of the neutral form in the entire acid region examined. First order rate law best fits the results in the entire acid range, leading to overall pseudo-first order rate coefficients in the medium used. Solvent and solvent-isotope effect studies support the existence and contribution of monoprotonated species formed by a specific acid catalysed reaction for this triester bimolecular mode of hydrolysis is derived by the application of Arrhenius equation and various correlations given by Bunnett and others. The P—N bond cleavage is confirmed by comparison of kinetic and thermodynamic parameters of the closely related triamidates.